Synthesis of Carboxymethyl Calix[4]arene Intercalated Layered Double Hydroxides - Lei Liu, Xiao (Asian Journal of Chemistry, 2013)
The intercalation of water-soluble carboxymethyl calix[4]arene (CMCS) in the interlayer of the Zn-Al layered double hydroxides powder and film by the anion exchange and in situ crystallization methods have been investigated. The XRD results confirm the intercalation of carboxymethyl calix[4]arene in the interlayer galleries of layered double hydroxides. In both powder and film samples, carboxymethyl calix[4]arene molecules adopt a monolayer arrangement, with the axis of the cavity perpendicular to the layered double hydroxides sheets. The SEM images indicate that the ab-face of layered double hydroxides microcrystals is predominantly perpendicular with respect to the porous anodic alumina substrate. Compared with the CMCS-LDHs powder sample, the structured CMCS-LDHs film exhibits the advantages of more convenient operation. This carboxymethyl calix[4]arene functionalized inorganic layered film may have potential application in the field of industrial adsorption, separation and inclusion.